Studies in Byzantine Epigraphy 1 - Rhoby, A (Brepols, 2023)
The Studies in Byzantine Epigraphy series testifies to an ever-greater focus on inscriptions within Byzantine Studies. The present, inaugural volume includes selected papers from the two panels dedicated to Byzantine Epigraphy held at the XXIII International Congress of Byzantine Studies in Belgrade, August 2016, and the XV International Congress of Greek and Latin Epigraphy in Vienna, August/September 2017. The papers, as indeed the events for which they were initially produced, celebrate both the progress and the promise of epigraphic research within medieval and early modern scholarship as a whole.